2012
DOI: 10.1146/annurev-ento-120709-144748
|View full text |Cite
|
Sign up to set email alerts
|

Approaches and Incentives to Implement Integrated Pest Management that Addresses Regional and Environmental Issues

Abstract: Agricultural, environmental, and social and policy interests have influenced integrated pest management (IPM) from its inception. The first 50 years of IPM paid special attention to field-based management and market-driven decision making. Concurrently, IPM strategies became available that were best applied both within and beyond the bounds of individual fields and that also provided environmental benefits. This generated an incentives dilemma for farmers: selecting IPM activities for individual fields on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
69
0
5

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 104 publications
(76 citation statements)
references
References 103 publications
2
69
0
5
Order By: Relevance
“…Such findings indicate powerful mechanisms available to farmers to favor beneficial insects by managing seminatural habitats at the farm level and, in contrast, less influential landscape features that farmers have less control over. Regarding the influence of landscape structure on trophic levels, several studies have demonstrated that predators and parasitoids appear to respond at smaller spatial scales than herbivorous insects (Brewer and Goodell 2012;O'Rourk et al 2010) and may be more susceptible to habitat fragmentation (Kruess and Tscharntke 2000). Complementarily, Thies et al (2003) argue for the general idea that higher trophic levels are more sensitive to landscape simplification, indicating a great need to analyze and understand the effect of landscape on biological regulations.…”
Section: Main Advances In Ecology To Characterize Biodiversity-based mentioning
confidence: 99%
“…Such findings indicate powerful mechanisms available to farmers to favor beneficial insects by managing seminatural habitats at the farm level and, in contrast, less influential landscape features that farmers have less control over. Regarding the influence of landscape structure on trophic levels, several studies have demonstrated that predators and parasitoids appear to respond at smaller spatial scales than herbivorous insects (Brewer and Goodell 2012;O'Rourk et al 2010) and may be more susceptible to habitat fragmentation (Kruess and Tscharntke 2000). Complementarily, Thies et al (2003) argue for the general idea that higher trophic levels are more sensitive to landscape simplification, indicating a great need to analyze and understand the effect of landscape on biological regulations.…”
Section: Main Advances In Ecology To Characterize Biodiversity-based mentioning
confidence: 99%
“…management of the landscape structure to promote beneficial associated diversity (Fig. 1c), requires coordination between stakeholders with different interests and adapted institutions (Brewer and Goodell 2010;Caron et al 2014;Darnhofer 2015;Duru et al 2015). The need to anticipate and manage cascade effects between organisational levels makes these landscape-level practices complex to implement (Duru et al 2015;Galloway et al 2008;Walker and Meyers 2004).…”
Section: Challenges Of the Transition To Biodiversity-based Agricultumentioning
confidence: 99%
“…The training emphasized IPM practices that mitigate the impacts of pest management activities on soil, water, air, plants and animals. This partnership with NRCS in California provided an opportunity to increase IPM adoption by linking activities to NRCS-recognized practices for cost sharing (Brewer and Goodell 2012). For example, as part of NRCS whole farm resource planning, the inclusion of an IPM plan was encouraged to identify potential mitigation activities related to pest management.…”
Section: New Focus New Pests 1986 To 2000mentioning
confidence: 99%